Assessment of Irrigation Water Quality Sourced from River Galma in Zaria, Nigeria - Yakubu, S.; Folorunsho, J. O.; Adeniyi, S. A. (NIU Journal of Social Sciences, 2017)
This study aimed at assessing the quality of irrigation water sourced from River Galma to irrigate farmlands in Zaria, located between latitudes 11 o 00’ to 11 o 12’N and longitude 07 o 36’ to 07 o 45’E. Irrigation water samples from River Galma used to irrigate the fadama land were collected from five different points for three consecutive times at the very points where the farmers use the water to irrigate their farms and tested for the following selected metals: chromium (Cr), lead (Pb), nickel (Ni), and arsenic (As). X-ray Fluorescence (XRF) spectroscopy which is an analytical technique was used to determine the metal contents of water samples. Analysis of variance was used to compare the result at 0.01 significant level. The results show the concentration of Cr, Pb, Ni and As as; 0.09, 0.04, 0.04 and 0.03mg/l respectively. Although Cr has the highest mean value and is significantly differentiated at the five sampling locations over the basin, the mean value is below the permissible limit for irrigation water by Nigeria’s Federal Environmental Protection Agency concentration of the selected metals was found to be tolerable for irrigation purpose. The study thus recommended that the quality of irrigation water should be investigated from time to time to avoid build-up of heavy metal that may be detrimental to health of both human and animal in the long run. Keywords: Water quality, Irrigation, River Galma, Metal content, Zaria